2015
DOI: 10.17795/jhealthscope-21137
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Index and Ecological Risk of Heavy Metals in the Surface Soils of Amir-Abad Area in Birjand City, Iran

Abstract: Background:In the present era, the concentration of heavy metals in the environment is increasing. Due to the deleterious effects of these metals on human health as well as their dangerous consequences on ecosystem, special attention should be paid to remove them from the environment. Objectives: The purpose of this study was to assess the ecological risk of heavy metals including lead (Pb), cadmium (Cd), copper (Cu), zinc (Zn), chromium (Cr) in surface soils of an Amir-Abad Area in Birjand City, Iran. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Heavy metals are mainly introduced into agricultural soils by pesticides, fertilizers, soil amendments, wastewater irrigation, and other scattered, diffuse pollution sources such as industry, traffic emissions, and incineration (3). Further, the mean concentrations of Pb and Cd in the surface soils around the factory were lower than their concentrations in the earth's crust (Cd: 0.2, Pb: 14 mg/kg) (29,30), indicating low contamination in the studied soils. Kamani et al (31) expressed that the low levels of lead in urban soils may be related to the banning of leaded gasoline in Iran.…”
Section: Discussionmentioning
confidence: 86%
“…Heavy metals are mainly introduced into agricultural soils by pesticides, fertilizers, soil amendments, wastewater irrigation, and other scattered, diffuse pollution sources such as industry, traffic emissions, and incineration (3). Further, the mean concentrations of Pb and Cd in the surface soils around the factory were lower than their concentrations in the earth's crust (Cd: 0.2, Pb: 14 mg/kg) (29,30), indicating low contamination in the studied soils. Kamani et al (31) expressed that the low levels of lead in urban soils may be related to the banning of leaded gasoline in Iran.…”
Section: Discussionmentioning
confidence: 86%
“…Various studies of ecological risk assessment showed that Pb caused various diseases in humans like kidney problems, liver diseases, and cancer (45,46). Thus, Pb can affect the local ecological function in the long run and currently, it does not have the ability to create health and environmental problems (47)(48)(49). So, it is important to consider the levels of heavy metals to inhibit the potential hazards of these metals in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely causes of high Pb concentrations in the study area are old automobiles driven with leaded petrol, the combustion of the diesel oil, and the manufacturing and metallurgical processes. 4 Health Scope. 2017; 6(1):e39241.…”
Section: Discussionmentioning
confidence: 99%
“…There are various anthropogenic sources and activities, which are responsible for releasing HMs into the atmosphere such as incomplete burning of multiple types of fuel in industrial activity, transportation and power plants. In contrast, transportation is recognized as the most important source of HMs in urban areas and has attracted increasing interest in this context (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%